Periodontitis and venous thromboembolism risk: Investigating the connection through a systematic review and meta-analysis - Pratama, Erlan Anugrah; Sadikaningtya, Lirasati; Indarto, Malik Jantra; Adi, Andi Wahjono; Siswanto, Bambang Budi (Heart Science Journal, 2025)
BACKGROUND: The relationship between periodontitis and venous thromboembolism (VTE) remains controversial. Some studies show an association, while others do not show an association between periodontitis and VTE. OBJECTIVES: This study aims to determine the relationship between periodontitis and the risk of VTE using a meta-analysis approach. METHODS: A meta-analysis study, registered in PROSPERO, was conducted from August to September 2024. The sources for article searches in this study were Scopus, Embase, and PubMed. Data on the proportion of VTE occurrences in the periodontitis and non-periodontitis groups were collected from each article, and pooled point estimates were calculated using the Mantel-Haenszel test. RESULTS: We identified 40,397 VTE cases and 2,215,063 controls from six articles. Among these six articles, three showed an association between periodontitis and an increased risk of VTE. Additionally, we identified one article reporting that periodontitis was associated with a decreased risk of VTE. Furthermore, two articles revealed that periodontitis had no association with VTE occurrence. Our calculations using the Mantel-Haenszel test showed that, overall, an increased risk of VTE was found in individuals with periodontitis compared to those without (RR: 1.61; 95% CI: 1.09 – 2.39; Egger's p: 0.7917; Heterogeneity p: <0.0001; p: 0.0200). CONCLUSION: We have identified that periodontitis is an important factor in the occurrence of VTE.